2021
DOI: 10.1038/s41598-021-83569-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autotaxin activity ameliorates neuropathic pain derived from lumbar spinal canal stenosis

Abstract: Lumbar spinal canal stenosis (LSS) or mechanical compression of dorsal root ganglion (DRG) is one of the causes of low back pain and neuropathic pain (NP). Lysophosphatidic acid (LPA) is a potent bioactive lipid mediator that is produced mainly from lysophosphatidylcholine (LPC) via autotaxin (ATX) and is known to induce NP via LPA1 receptor signaling in mice. Recently, we demonstrated that LPC and LPA were higher in cerebrospinal fluid (CSF) of patients with LSS. Based on the possible potential efficacy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Encouraged by the evidence that ATX and LPA levels are increased upon neuronal injury and that production of LPA up-regulates pain-related proteins through the LPA1 receptor, we were particularly interested in developing an ATX inhibitor for neuropathic pain. Very recently, it was reported that an ATX inhibitor ONO-8430506 could ameliorate neuropathic pain symptom in CD rat model at 30 mg/kg, , which further strengthens this hypothesis. Our initial screening of an internal lipid mimetic chemical library derived from our previous S1P work and subsequent optimization identified a hit compound 5 (Figure ), a phosphonic acid-based inhibitor that inhibits ATX in the FRET assay with good potency (IC 50 = 28 nM).…”
supporting
confidence: 56%
“…Encouraged by the evidence that ATX and LPA levels are increased upon neuronal injury and that production of LPA up-regulates pain-related proteins through the LPA1 receptor, we were particularly interested in developing an ATX inhibitor for neuropathic pain. Very recently, it was reported that an ATX inhibitor ONO-8430506 could ameliorate neuropathic pain symptom in CD rat model at 30 mg/kg, , which further strengthens this hypothesis. Our initial screening of an internal lipid mimetic chemical library derived from our previous S1P work and subsequent optimization identified a hit compound 5 (Figure ), a phosphonic acid-based inhibitor that inhibits ATX in the FRET assay with good potency (IC 50 = 28 nM).…”
supporting
confidence: 56%
“…Beta-actin were used as [15]. LPA, a potent bioactive lipid mediator, is mainly produced from lysophosphatidylcholine (LPC) via autotaxin (ATX) [1]. Therefore, we examined the expression of LPA, LPC, and ATX in CSF of different patients.…”
Section: Isolation and Primary Culture Of Spinal Cord Neuronsmentioning
confidence: 99%
“…Lumbar spinal stenosis (LSS) is a common spinal degenerative clinical disease and one of the clinical manifestations of neuropathic pain [ 1 ]. Most symptoms of LSS are attributed to compression of the spinal cord, nerve roots, or cauda equina [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrathecal LPC-induced mechanical allodynia and thermal hyperalgesia were significantly reduced in autotaxin heterozygous animals, indicating reduced conversion of LPC to LPA [ 104 ]. Moreover, ATX inhibition could ameliorate neuropathic pain symptoms by using ATX inhibitor (ONO-8430506) [ 109 ]. In addition, a recent study demonstrated that nerve injuries induced the production of LPA by converting LPC to LPA under the action of ATX, which was observed only in the spinal dorsal horn, but not in the spinal nerve, sciatic nerve, or DRG, for several hours.…”
Section: Lysophosphatidylcholine and Chronic Pain Diseasesmentioning
confidence: 99%